Tutankhamun - Green, Robert, 1969- (New York : Franklin Watts, 1996)
Tells the story of the discovery of Tutankhamun's tomb by Howard Carter and Lord Carnarvon and the supposed curse connected with it, as well as information on the life and dynasty of the pharaoh.
Includes bibliographical references (p. 61-62) and index.
Keywords: Tutankhamen, -- King of Egypt -- Tomb -- Juvenile literature; Tutankhamen, -- King of Egypt -- Juvenile literature; Tutankhamen, -- King of Egypt -- Tomb; Egypt -- Antiquities -- Juvenile literature; Egypt -- Antiquities